Prognostic value of preoperative left ventricular global longitudinal strain for predicting postoperative myocardial injury and mortality in patients undergoing major non-cardiac surgery (SOLOMON study). (1st May 2023) - Kim, Minkwan; Moon, Inki; Bae, SungA; Seo, HyeSun; Jung, In Hyun
Abstract: Background: The usefulness of preoperative measurement of left ventricular global longitudinal strain (LVGLS) for predicting prognosis in patients undergoing non-cardiac surgery has not been evaluated. We analyzed the prognostic value of LVGLS in predicting postoperative 30-day cardiovascular events and myocardial injury after non-cardiac surgery (MINS). Methods: This prospective cohort study was conducted in two referral hospitals and included 871 patients who underwent non-cardiac surgery <1 month after preoperative echocardiography. Those with ejection fraction <40%, valvular heart disease, and regional wall motion abnormality were excluded. The co-primary endpoints were the (1) composite incidence of all-cause death, acute coronary syndrome (ACS), and MINS and (2) composite incidence of all-cause death and ACS. Results: Among the 871 participants enrolled (mean age: 72.9 years; female: 60.8%), there were 43 cases of the primary endpoint (4.9%): 10 deaths, 3 ACS, and 37 MINS. Participants with impaired LVGLS (≤16.6%) had a higher incidence of the co-primary endpoints (log-rank P  < 0.001 and 0.015) than those without. The result was similar after adjustment with clinical variables and preoperative troponin T levels (hazard ratio = 1.30, 95% confidence interval [CI] = 1.03–1.65; P  = 0.027). In sequential Cox analysis and net reclassification index, LVGLS had an incremental value for predicting the co-primary endpoints after non-cardiac surgery. Among the 538 (61.8%) participants who underwent serial troponin assay, LVGLS predicted MINS independently from the traditional risk factors (odds ratio = 3.54, 95% CI = 1.70–7.36; P  = 0.001). Conclusions: Preoperative LVGLS has an independent and incremental prognostic value in predicting early postoperative cardiovascular events and MINS. Clinical Trial Registration : URL: https://trialsearch.who.int/ . Unique identifiers: KCT0005147. Highlights: LVGLS is independently associated with the early postoperative outcomes. Preoperative LVGLS has incremental value in predicting cardiovascular events. LVGLS had good diagnostic performance on myocardial injury after noncardiac surgery Assessing LVGLS may be useful in predicting cardiovascular events and MINS